DISTINCTIVE FEATURES OF THE 'TALQINCHAI SAVTI KALOM' DIRECTION IN UZBEK CLASSICAL MUSIC PERFORMANCE - Abdulhay Karimov (Innovate Conferences, 2025)
The article discusses the features of the "Talkinchai savti kalom" direction in Uzbek classical music performance, the fact that this type of music has been formed over the centuries, improved in content and form, and that each direction, each style in classical music performance is distinguished by its own rules of performance, spiritual and philosophical load and cultural significance.